2016
DOI: 10.1016/j.clinph.2015.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Tongue electrical impedance in amyotrophic lateral sclerosis modeled using the finite element method

Abstract: Objective Electrical impedance myography (EIM) of the tongue has demonstrated alterations in patients with amyotrophic lateral sclerosis (ALS) compared to normal subjects. Whether these differences are due to reduced tongue size or diseased-associated alterations in the electrical characteristics of intrinsic tongue muscles is uncertain. Methods We employed computer simulations using the finite element method, inputting data from healthy and ALS mouse muscle, to help answer that question, comparing our model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The modelling work of Pacheck et al, indicates tongue volume has little impact on impedance data and we were recording in the midline of the tongue blade and hence not near the muscle edge. (Pacheck et al , 2016). We therefore consider that it is unlikely that our results are explained by differences in tongue volume.…”
Section: Resultsmentioning
confidence: 78%
“…The modelling work of Pacheck et al, indicates tongue volume has little impact on impedance data and we were recording in the midline of the tongue blade and hence not near the muscle edge. (Pacheck et al , 2016). We therefore consider that it is unlikely that our results are explained by differences in tongue volume.…”
Section: Resultsmentioning
confidence: 78%
“…EIS can detect changes in the shape and structure of the cells within the tissue [1][2][3]. This property has been used to aid the early detection of cervical cancer [1,2,4] and is being explored in the oral cavity to detect oral cancer and its potential use in detection of multiple sclerosis [5][6][7]. Other early studies have investigated its ability to identify cancer in prostate, bladder and breast tissues [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed this effect in rats, in which we witnessed reductions in reactance and resistance as young animals matured, despite their having larger myofiber cross sectional area [ 27 ]. More recently, we have modeled this effect in the human tongue and similarly observed that increasing muscle size alone, keeping all other parameters identical, causes reductions in the measured resistance and reactance [ 28 ]. This also is due to a lower current density in the region of the voltage electrodes.…”
Section: Discussionmentioning
confidence: 99%